Social Bodies and Identity of an Individual under the Influence of Techne and Logos - Ginevičius, Romualdas (Problemos, 2008)
The article deals with the social space that is influenced by different social bodies as an environment of individual’s existential becoming. Logos is interpreted as a whole of particular social attitudes, techne – as an art of existential creation. The next theses are developed: bodyness of the social groups presupposes a polyphonic environment of individual’s existential becoming; an acting and suffering individual existing bodily from birth until death is the constitutional analog and participant of the social group. The authors state that an individual realizing his existential project is a tie of the different community’s intersection and connecting chain of society. As far as there is no one society’s logos that intersect the all social environments, the existing individual become both their connecting tie and a factor of social horizon’s development. According to the authors, a society makes up a unit organism not having an environment of common logos, but including becoming individuals that connect the different logos with help of their existential project. The authors state that existential creation demands the skills of existential choice in the polyphonic changing logos’ environment of social bodies’ interconnection. The article deals with the role of philosophy in a technical university, as well. According to the authors, philosophical discourse is a special one regarding the other theoretical discourses, because it guaranties the transition from one existential-sensual province to the other one. Philosophical discourse evokes the thought’s fight and pushes the development of other theoretical discourses, i.e. helps to overcome their closeness.